Marital Division of Labor with Risk of Divorce: The Role of "Voice" Enforcement of Contracts - Lommerud, Kjell Erik (Journal of Labor Economics, 1989)
It is assumed that emotional ties can be relied on to enforce implicit marital contracts by "voice." Therefore, in the present model, divorce has economic consequences not only because the economies of scale from living together are destroyed but also because the scope for such "voice" enforcement is weakened. Moreover, perhaps surprisingly, I find that it is ambiguous how an increase in the probability of divorce influences predivorce allocation of time, even when preferences are assumed to be homothetic.